Effect of Nd3+ Ion Concentration on the Corrosion Resistance of API X70 Steel in Chloride-Rich Environments - D. M. Martinez de la Escalera; J. J. Ramos-Hernandez; E. Porcayo-Palafox; J. Porcayo-Calderon; J. G. Gonzalez-Rodriguez; L. Martinez-Gomez (Advances in Materials Science and Engineering)
In this study, the effect of the addition of Nd3+ ions as a corrosion inhibitor of the API X70 steel in a medium rich in chlorides was evaluated. The performance of the Nd3+ ions was evaluated by means of electrochemical techniques such as potentiodynamic polarization curves, open circuit potential measurements, linear polarization resistance, and electrochemical impedance spectroscopy, as well as by means of scanning electron microscopy and EDS measurements. The results showed that Nd3+ ions reduce the corrosion rate of steel at concentrations as low as 0.001 M Nd3+. At higher concentrations, the inhibition efficiency was only slightly affected although the concentration of chloride ions was increased by the addition of the inhibitor. The adsorption of the Nd3+ ions promotes the formation of a protective layer of oxides/hydroxides on the metal surface, thereby reducing the exchange rate of electrons. Nd3+ ions act as a mixed inhibitor with a strong predominant cathodic effect.